PERAN MASJID DALAM MENINGKATKAN EKONOMI MASYARAKAT - Saudi, R M Irfan; Hidayat, Hidayat; Walian, Anang (Yonetim Jurnal, 2024)
This research is entitled The Role of Mosques in Increasing Community Economic Empowerment in Muara Pinang District, Empat Lawang Regency. The background is the problem of trying to manage mosques as a place for economic and social empowerment. The aim of this research is to find out the role of mosques in increasing community economic empowerment in Muara Pinang District and to determine the inhibiting and supporting factors for mosques in improving the community economy in Muara Pinang District. The research method used in this research is qualitative analysis, with data collection techniques through observation, interviews and documentation. The results of the research show firstly, the role of the mosque in increasing the economic empowerment of the community in Muara Pinang District, Empat Lawang Regency, namely as a center for social and educational services for the congregation to increase awareness of the community around the mosque so that with the economic empowerment of the community at the Baiturrahman Mosque it can help people who have no income permanent, as well as strengthening community friendship and increasing the economic and social community's concern for local neighbors who are in need. Second, there is very good community participation, there are fund activity programs aimed at the community's economy and there are donations from various aid.